Balance Of Price Fairness And Industrial Protection (Analysis of the Impact of Import Tariff Policy on Domestic Consumer Goods from an Islamic Economic Perspective) - Nurlaili Janati; Ferlita Hanifah; Lamby Mahdalena Mirawati; Yusnidar Via Amanda (El-Ghiroh : Jurnal Studi Keislaman, 2025)
The import tariff policy implemented by the Indonesian government aims to protect domestic industries. However, this policy often results in rising consumer goods prices and weakening public purchasing power. This study aims to analyze the impact of import tariff policies on domestic consumer goods prices from an Islamic economic perspective, specifically regarding the principles of price justice, the welfare of the people, and protection of local producers (?im?yah al-mustahlik wa al-muntij). The approach used is qualitative through a literature study sourced from data from the Central Bureau of Statistics, academic literature, and Islamic economic principles. The results show that the consistent application of import tariffs causes price increases for basic consumer goods such as food and beverages, which impacts inflation and reduces the welfare of low-income communities. From an Islamic economic perspective, tariff policies should be based on the principles of justice and balance, so that they can protect national industries without causing dharar (loss) to consumers. Therefore, a balanced policy formulation is needed between the interests of industry and the needs of society to achieve a fair and sustainable trading system.